AB0092 Downregulation of immunoglobulinlike transcript 4 (ilt4) in patients with rheumatoid arthritis. (23rd January 2014) - Chimenti, M. S.; Bergamini, A.; Baffari, E.; Greco, E.; Gigliucci, G.; Guarino, M. D.; Perricone, R.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by destruction of juxtaarticular cartilage and bone due to excessive activation of inflammatory cells of which the underlying mechanisms are not fully elucidated. Macrophages may play a major role in the process of inflammation and tissue destruction since they are the predominant source of interleukin (IL)-1β and tumor necrosis factor (TNF)-α that are central to the pathogenesis of RA. Leukocyte immunoglobulin-like receptors (LILRs) are emerging as critical regulators of the threshold and amplitude of leukocyte activation, and perturbed expression of LILRs may contribute to uncontrolled inflammation (1 ). In particular, the inhibitory LILR-2, also called the immunoglobulinlike transcript 4 (ILT4), which is predominantly expressed on macrophages, provides inhibitory signals (2 ). Thus, it is tempting to speculate that decreased ILT4 expression on macrophages in RA may lead to a chronic activation of these cells and thereby result in exaggerated inflammation. Objectives: To investigate the expression of ILT4 and the relationship between ILT4 and pro-inflammatory cytokine production in monocytes from RA patients before and after anti-TNF-a therapy. Methods: Surface expression of ILT4 and lipopolysaccharide (LPS)-induced TNF-a and IL-1b production were analysed by FACS on circulating monocytes from 13 patients with RA and 10 age and sex matched healthy controls, before and after 12-weeks therapy with anti-TNF-a mAb. Results: ILT4 expression was significantly decreased on both CD14 + /CD16 - and CD14 - /CD16 + monocytes from RA patients as compared to controls. In addition, a significant reduction in the ability to upregulate ILT4 surface expression under condition of activation by granulocyte-macrophage colony stimulating factor (GM-CSF) was documented in moncytes from RA patients with respect to cells from controls. Monocytes from both, patients and controls, did not spontaneously produce proinflammatory cytokines. However, after LPS stimulation TNF-a and IL-1b production was significantly increased in patients compared to controls. This increased cytokine response was not due to a enhanced susceptibility of monocytes from RA patients to LPS but rather to an expansion of the ILT4 - monocyte subset, since TNF-a and IL-1b expression was almost exclusively observed in this cell subset. Twelve-weeks treatment with anti-TNF-a mAb resulted in a significant increase of monocyte ILT4 expression, ILT4 response to GM-CSF activation and in a significantly reduced proinflammatory cytokine expression, compared with pre-therapy levels. Conclusions: The finding that RA patients display a low expression of monocytic ILT4, which may lead to more severe tissue damage and impairment of the control of autoreactive cells by upregulating the proinflammatory and antigen-presenting functions of monocytes, suggests that drugs targeting this molecule may have significant therapeutic value for the management of patients. References: Colonna M, et al. J Exp Med. 1997;186:1809-18 Chang CC, et al. Nat Immunol 2002;3:237-43 Disclosure of Interest: None Declared